The chronotope of the primordial: Yuri Rytkheu’s When the whales leave - Mørch, Audun (Nordlit, 2014)
Yuri Rytkheu (1930-2008) is a Chukchi novelist who wrote in Russian. During recent years his works have been published into German, English and other languages. His popularity outside Russia is rising. The present article introduces the reader to Rytkheu and his works and goes on to a reading of When the Whales Leave (1977), a short novel written in the form of a family saga with many elements from the author’s native Chukchi myth. Special attention is given to chronotopic properties of the work. The article also argues that When the Whales Leave draws attention to ecological problems and represents an indirect critique of the European (Christian) Weltanschauung, where man is the master of nature rather than a part of it.